The Current Dynamics of Employee Performance Publication: A Bibliometric Analysis in the Globalized Business Landscape - Ekawati, Adinda; Nuryasti, Nabila (Jurnal Ilmiah Manajemen Kesatuan, 2023)
In the era of globalization, high performance is crucial for companies to stay competitive. Effective management of human resources plays a vital role in achieving organizational goals. This study focuses on employee performance and aims to classify the topics related to it, identify trends, and evaluate promising themes for future research. The research methodology includes bibliometric analysis and the use of VOSviewer software. The findings reveal that topics such as work motivation, work discipline, compensation, competence, organizational culture, leadership style, and employee management are relevant and influential in employee performance. Understanding and addressing these factors can contribute to the success of organizations in today’s highly competitive business. The findings of this study underscore the multifaceted nature of factors influencing employee performance, offering valuable insights for organizations striving to enhance their competitiveness. By highlighting key themes such as work motivation, work discipline, and organizational culture, this research provides a roadmap for future studies, contributing to a comprehensive understanding of the intricacies involved in managing human resources for optimal performance in a globalized business environment.